IMPLEMENTASI SISTEM PRESENSI ONLINE BERBASIS WEB DENGAN GEO-TAGGING MENGGUNAKAN METODE HAVERSINESTUDI KASUS PT WIFIKU INDONESIA - Egano Syaban Albanu; Dimas Abisono Punkastyo (Journal of Research and Publication Innovation, 2026)
The high mobility of Technical Support employees at PT WiFiku Indonesia creates challenges in attendance and leave processes that are still handled manually, resulting in difficulties in validating attendance locations, delays in data recapitulation, and increased risk of administrative errors. This study aims to design and implement a web-based online attendance system that facilitates flexible attendance and leave submission from work locations while supporting centralized monitoring by the Human Resource Development (HRD) department. The research method used is descriptive qualitative, conducted through observation, interviews, and literature review, with system development applying the Extreme Programming method, which includes planning, design, coding, and testing stages. The system utilizes geo-tagging to record attendance location coordinates and the Haversine method to calculate the distance between the attendance location and the designated work-area point as a radius-based validation mechanism, and is equipped with visual proof in the form of selfie photos as well as check-in and check-out features. The results show that the developed system is able to record attendance and leave data in a structured manner, validate attendance according to work placement areas, and accelerate monitoring and data recapitulation processes by HRD. This study concludes that the implementation of a geo-tagging-based online attendance system using the Haversine method improves the efficiency, accuracy, and transparency of attendance management for field employees and has the potential to serve as an adaptive attendance solution for companies with onsite work characteristics.